Tolerance of 20 heirloom rice varieties at seedling stage salinity stressed and their growth in lowland coastal area - Rustikawati, Rustikawati; Herison, Catur; Chozin, Muhammad; Indres, Indres (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2020)
Coastal area of Bengkulu Province is home of many heirloom rice varieties and play an important role in contributing rice production in the province. However, as the climate change proceeds, a progressive sea water inundation has increased soil salinity mainly in low-lying areas and jeopardizing the sustainability of rice production in coastal regions. The use of salt-tolerant varieties, therefore, would be a sensible solution to alleviate the adverse effect of soil salinity in respect of maintaining the crop production in the coastal areas. The objective of this study was to examine the salinity tolerance of 20 heirloom rice varieties collected from a coastal area of Bengkulu Province. Prior to the screening process, lethal concentration 90 (LC90) was determined by assaying the seedlings of ‘Kuning Tinggi’ in a series of nutrient solution containing a different concentration of NaCl (0, 2000, 4000, 6000, 8000 and 10000 ppm). Using a regression analysis, LC90 was detected at a concentration of 3910 ppm. The screening was performed by exposing the varieties in the nutrient solution culture containing 4000 ppm NaCl and growing them on the tidal swamp. Under nutrient culture evaluation, the symptom of NaCl toxicity was scored and converted to salinity tolerance index. ‘Humbur’, ‘Kuning Tinggi’ and ‘Padang Bakung’ exhibited medium tolerant, while ‘Beram’, ‘Imperata’ and ‘Kuning’ exhibited very sensitive. Further evaluation of the tidal swamp for vegetative and generative performances signified that ‘Humbur’ and ‘Kuning Tinggi’ had medium tolerant to salinity stress